ANALISIS KEUNTUNGAN USAHATANI CABAI MERAH KERITING CV FAREL DI KELURAHAN KAKASKASEN II KECAMATAN TOMOHON UTARA KOTA TOMOHON (Profit Analysis of Red Curly Chili Farming of â€œCV. Farelâ€ at Kakaskasen II of North Tomohon District, Tomohon City) - Jerlin Beatric Makausi; Benu O. L. Suzana; Ribka M. Kumaat (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2021)
This study aimed to analyze the profits of CV Farel's curly red chili farming in Kakasksen II, North Tomohon District, Tomohon City. The method used in this research was descriptive method, and applied the profit analysis.The results showed that Curly Red Chili Farming of CV. Farel earned a profit of Rp.41,354,000.- with a total cost of Rp. 25,646,000. The calculation of efficiency analysis produces an R/C Ratio value of 2.61. This showed that the farming was efficient because the value of R/C Ratio > 1, where every 1 (one) rupiah spent would produce 2.61 rupiah.